Yoga Training in Junior Primary School-Aged Children Has an Impact on Physical Self-Perceptions and Problem-Related Behavior - Richter, Stefanie; Tietjens, Maike; Ziereis, Susanne; Querfurth, Sydney; Jansen, Petra (Frontiers in Psychology, 2016)
The present pilot study investigated the effects of yoga training, as compared to physical skill training, on motor and executive function, physical self-concept and anxiety-related behavior in junior primary school-aged children. Twenty-four participants with a mean age of 8.4 (± 1.4) years completed either yoga or physical skill training twice a week for six weeks outside of regular school class time. Both forms of training were delivered in an individualized and child-oriented manner. The type of training did not result in any significant differences in movement and executive function outcomes. In terms of physical self-concept, significant group differences were revealed only for perceived movement speed such that yoga training resulted in perceptions of being slower while physical skill training resulted in perceptions of moving faster. Analysis of anxiety related outcomes revealed significant group effects only for avoidance behavior and coping strategies. Avoidance behavior increased following yoga training, but decreased following physical skill training. In addition, following yoga training, children showed an increased use of divergent coping strategies when facing problematic situations while after physical skill training children demonstrated a decrease in use of divergent coping strategies. Increases in overall physical self-concept scores were significantly correlated with increases in avoidance behavior following yoga training. In contrast, following physical skill training increased physical self-concept was significantly correlated with decreases in avoidance behavior. In sum, exposure to yoga or physical skill training appears to result in distinct effects for specific domains of physical self-concept and anxiety-related behavior. Further studies with larger samples and more rigorous methodologies are required to further investigate the effects reported here. With respect to future studies, we address potential research questions and specific features associated with the investigation of the effects of yoga in a sample of school-aged children.